FORM AND FUNCTION IN ENGLISH LANGUAGE TECHING AT STATE POLYTECHNIC OF SRIWIJAYA - Sri Gustiani (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2011)
Learners of English are required to have competences in form and function in order to be able to communicate or read effectively in English. Teachers of English who conduct the process of language learning in English language teaching classroom need to aware about this situation. They need to know what method or approach to use to facilitate students gaining these competences. The combination of form and function-focussed teaching is another alternative to meet the competence of English language learners both in form and function. Focusing on students’ needs, the knowledge of form and function remains teacher to adapt or even combine the existed English Language Teaching method/approach.